2011
DOI: 10.14236/ewic/hci2011.46
|View full text |Cite
|
Sign up to set email alerts
|

A Taxonomy of Number Entry Error

Abstract: People are prone to errors in many aspects of life, including when entering numbers. The effects of these errors can be disastrous, for example when an incorrect number is entered when programming a medical infusion pump or when entering financial information into a system. Designing better systems may help to prevent these errors however, in order to do this we need to understand far more about the types of errors being made, and their causes. Unfortunately, there are very few documented examples of number en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…By pressing the Enter key the current displayed number was saved and at the same time the display was cleared. The display itself provided participants to enter a 5-digit number with two digits after a separating decimal point as previously gathered numbers from infusion pump logs confirmed the validity of this number range [19]. There were three versions of the interface used in the study.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…By pressing the Enter key the current displayed number was saved and at the same time the display was cleared. The display itself provided participants to enter a 5-digit number with two digits after a separating decimal point as previously gathered numbers from infusion pump logs confirmed the validity of this number range [19]. There were three versions of the interface used in the study.…”
Section: Methodsmentioning
confidence: 84%
“…Previous studies have shown that human errors are the source of more than 50% of incidents in most domains and in aviation can be as high as 90% [20]. In healthcare the process of studying errors is only now emerging [19]. Recent studies have shown that people make transcription errors frequently and many systems do little to detect and prevent errors [18].…”
Section: Introductionmentioning
confidence: 99%
“…This makes the decimal point prominent in the GR (see Fig. 2c), as decimal point related errors are serious and common (Oladimeji et al, 2011;Wiseman et al, 2011).…”
Section: Constructing Graphical Number Representationsmentioning
confidence: 99%
“…Visual checking is a widely adopted method due to its advantages of high user preference and short execution time (Barchard and Pace, 2011; Barchard and Verenikina, 2011;Wiseman et al, 2011). Checking simply requires to compare entries with instructions to determine if they match.…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple parameters that could be required during a typical programming sequence including the Volume to Be Infused (VTBI), the rate of infusion and/or the time taken to complete an infusion (Furniss, Blandford, Rajkomar, Vincent, & Mayer, 2011). Figure 4 outlines an illustrative and simplified representation of design decisions corresponding to the specification of number entry input (for a more in detailed treatment see (Campos & Harrison, 2011;Cauchi et al, 2011;Masci et al, 2011;Oladimeji, Thimbleby, & Cox, 2011;Thimbleby & Cairns, 2010;Wiseman, Cairns, & Cox, 2011)).…”
Section: Qoc-e: Assertions and Evidencementioning
confidence: 99%